Development Of Ppkn Interactive E-Module To Increase High School Students' Understanding Of Threats To The Position Of The Republic Of Indonesia - Estiva Estiva; Suyato Suyato (Yayasan Adra Karima Hubbi, 2024)
This research aims to develop a PPKn Interactive E-Module to increase students' understanding of SMA Negeri 1 Malinau regarding threats to the position of the Republic of Indonesia. It is hoped that the use of innovative learning media can improve the quality of learning and students' understanding of the material being taught. The development of this E-Module uses the ADDIE method, which consists of five stages: Analysis, Design, Development, Implementation and Evaluation. The final product is tested for suitability by experts. The material expert's assessment resulted in an average score of 3.8 with a percentage of 95%, which is in the